The Effectiveness of Physical Activity Training on Depersonalization and lack of accomplishment of Employees - Ali Vafaee najar; Mohammad Vahedian-Shahroodi; Hadi Tehrani; Mitra Dogonchi; Elahe Lael-monfared (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: Human in this period in the adaptability to the environment and his/her job is forced to undergo constraints and pressures. If we have extreme job stress, it can create physical, mental, behavioral complications for the individual, and in turn jeopardize his/her health. The objective of this study is to assess the effectiveness of physical activity training on worker burnout. Methods: In this semi-experimental study, which was carried out among 200 employees of Electricity Office, City Hall, the Governor and the Department of Education of Agh Ghala county, north of Iran. The employees were selected by random sampling. A three-part questionnaire (Demography, International Physical Activity Questionnaire (IPAQ), Maslach Burnout Inventory (MBI)) was used for collecting data. Data were analyzed using SPSS16 and descriptive statistics and independent t test, paired t test, Pearson correlation coefficient and ANOVA test significant level was considered 0.05 in all analyses.  Results: 57.5% of the employees were men and 91% were married. Average age was 38.52±7.86 years. Results showed that the mean of physical activity had increased after the intervention and with the increase in physical activity the mean of lack of job accomplishment decreased, which in turn shows increase in employees' job satisfaction. And with the decrease in the mean of depersonalization, employees' relationship with coworkers and those receiving services improved.  Conclusion: Physical activity is one of the ways of reducing depersonalization and lack of accomplishment among employees. Paper Type: Research Article.